International taxation – tax avoidance, its effects and preventive measures - Ščepanika, Sabīne (Riga Graduate School of Law, 2022)
Multinational Companies are using treaties between states to enter into schemes for tax avoidance and tax evasion. It is done by shifting profits to jurisdictions where is no tax or low tax, which is called “treaty shopping”, as well as through transfer pricing intra-group, hybrid mismatches and limiting interest deduction. As a response the OECD have issued a guidance on how to tackle tax avoidance, as it’s negative effects are impacting the government tax revenue, therefore, preventing government to fulfil its duties for developing economic and social welfare. In this paper is reviewed the tax avoidance tactics and its effects, the proposed guidance for tackling tax avoidance and the adopted legislation in the EU. Analysis is provided on how Covid-19 crisis have affected the tax policies and guidance in tax avoidance prevention. And landmark cases in relation of tax avoidance are presented to understand the milestones that have been already made in tackling tax avoidance.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; International taxation; Tax avoidance; Anti-Tax Avoidance Directive